State-Owned Enterprises Reform and Dual Office Holding: A Comparative Legal and Governance Analysis of Indonesia and Selected African Countries - Shanti Wulandari; Uche Nnawulezi (PATTIMURA Legal Journal, 2026)
Introduction: State-Owned Enterprises (SOEs) play a crucial role in national economic development, yet many face inefficiency, political interference, and governance challenges. The dual office holding phenomenon where public officials occupy positions within SOEs often intensifies conflicts of interest and reduces accountability. Reforming SOEs, therefore, becomes essential to balance political influence with corporate autonomy and transparency. Purposes of the Research: This study aims to analyze how Indonesia and selected African countries have undertaken SOE reforms while addressing the problem of dual office holding. It explores the institutional mechanisms, legal frameworks, and political dynamics influencing reform outcomes. The research seeks to provide comparative insights into best practices that promote effective governance and minimize political entanglement. Methods of the Research: The study employs a qualitative comparative approach, utilizing document analysis, policy review, and semi-structured interviews with policymakers and governance experts. By examining legislative reforms, administrative structures, and case examples, the research identifies patterns and differences in SOE governance models. Comparative data from Indonesia and three African nations underpin the analysis of institutional performance. Results Main Findings of the Research: Findings reveal that successful State-Owned Enterprises (SOEs) reforms depend on institutional independence, legal clarity, and enforcement against dual office practices. Indonesia shows progress through regulatory refinement, while African cases highlight persistent political patronage. Comparative analysis suggests that transparency mechanisms and merit-based appointments significantly enhance accountability and efficiency in state enterprise management.